Dislocation–Twin Boundary Interactions Induced Nanocrystalline via SPD Processing in Bulk Metals - Zhang, Fucheng (Sci Rep, 2015)
This report investigated dislocation–twin boundary (TB) interactions that cause the TB to disappear and turn into a high-angle grain boundary (GB). The evolution of the microstructural characteristics of Hadfield steel was shown as a function of severe plastic deformation processing time. Sessile Frank partial dislocations and/or sessile unit dislocations were formed on the TB through possible dislocation reactions. These reactions induced atomic steps on the TB and led to the accumulation of gliding dislocations at the TB, which resulted in the transition from coherent TB to incoherent GB. The factors that affect these interactions were described, and a physical model was established to explain in detail the feasible dislocation reactions at the TB.